Operative obstetrics - Gilstrap, Larry C., III; Cunningham, F. Gary; VanDorsten, J. Peter (McGraw-Hill, Medical Pub. Division, 2002)
Covering obstetrical procedures, this guide brings you step-by-step instructions for each major surgical procedure performed in obstetrical practice. With more than 470 illustrations, it includes 1,000 questions and answers.